2017
DOI: 10.1111/joim.12655
|View full text |Cite
|
Sign up to set email alerts
|

Integrative studies implicate matrix metalloproteinase‐12 as a culprit gene for large‐artery atherosclerotic stroke

Abstract: Our study supports the notion that MMP12 is implicated in large-artery atherosclerotic stroke, functionally by enhancing elastin degradation and macrophage invasion in plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 44 publications
3
31
1
3
Order By: Relevance
“…As an example of discrepancies between observational and MR estimates, we found serum levels of MMP12 to be increased in T2DM, consistent with previous reports 18 , whereas the MR estimate for MMP12 suggested a protective effect for T2DM. These findings are similar to the reported protective MR estimate for MMP12 and risk of coronary heart disease 19 whereas clinical and experimental studies have shown higher levels of MMP12 in cardiovascular disease 18,20 .…”
Section: Resultssupporting
confidence: 89%
“…As an example of discrepancies between observational and MR estimates, we found serum levels of MMP12 to be increased in T2DM, consistent with previous reports 18 , whereas the MR estimate for MMP12 suggested a protective effect for T2DM. These findings are similar to the reported protective MR estimate for MMP12 and risk of coronary heart disease 19 whereas clinical and experimental studies have shown higher levels of MMP12 in cardiovascular disease 18,20 .…”
Section: Resultssupporting
confidence: 89%
“…Several published MR findings were confirmed, including that IL6RA variants associated with higher circulating levels of interleukin-6 (IL-6) and soluble IL6-RA were associated with lower risk of coronary heart disease (CHD), rheumatoid arthritis (RA) and atrial fibrillation but higher risks of atopy, such as asthma and eczema 19 . We also replicated previous findings suggesting a causal contribution of IL-1ra to rheumatoid arthritis (RA) but an inverse causal relationship with cholesterol levels 20 , and a protective role of genetically higher MMP-12 against stroke 4,21 .…”
Section: Resultssupporting
confidence: 89%
“…Similarly, in vitro macro-calcification has been shown to increase cellular resistance to fluid sheer stress through enhanced cell-matrix interactions [35] and SMCs have a well-documented capacity to respond to physical forces and mechanical stretch [36]. Previous studies have already demonstrated elevated serum-titers of degraded elastin in patients with symptomatic carotid stenosis [37], increased stroke risk associated with low carotid plaque elastin content [38,39], and reduced elastin expression in plaques from S vs. AS patients [40].…”
Section: Discussionmentioning
confidence: 99%